4CPS-212 Healthcare providers' views of pharmacy team involvement in the preparation and administration of medicines on inpatients wards: an exploratory study. (24th March 2020) - Vella, EM; Cutajar, A; Lewis, P
Abstract : Background and importance: Lack of nursing staff, interruptions when preparing and administering medicines, and lack of knowledge can increase the risk of medication errors. The involvement of the pharmacy team in the preparation and administration of medicines on hospital wards has been highlighted as an opportunity to provide better guidance and support to nurses, enhance patient safety and improve service delivery. However, to date there is no evidence on this development in our country. Aim and objectives: To explore indepth the views of healthcare professionals towards pharmacy team (pharmacists and pharmacy technicians) involvement in the preparation and administration of medications on inpatient wards in a general hospital. Material and methods: Semi-structured, one to one interviews were conducted with a purposive sample of various healthcare professionals from the country's main general hospital between February and June 2018. A topic guide was developed to explore the acceptability and extent of involvement, including related limitations and benefits. The interviews were audio recorded, transcribed verbatim and analysed using framework analysis. Ethical approval was obtained from the participating hospital. Results: Thirteen healthcare providers from various clinical areas (medicine, surgery, critical care and emergency) were interviewed: two pharmacists, three pharmacy technicians, seven nurses and one doctor. Interviews lasted on average 20 min. All participants had overall positive views towards pharmacy team involvement. However, there were mixed opinions on the extent of involvement. All participants (with the exception of both clinical pharmacists) agreed that pharmacists and pharmacy technicians can be directly involved by administering oral medications and reconstituting medicines on wards. However, clinical pharmacists felt that direct involvement may be intrusive to nurses. Therefore, they suggested that pharmacists can be indirectly involved by providing advice on preparation/administration processes and in identifying and solving incompatibilities. The perceived benefits of such involvement were less errors and delayed treatment. However, limitations of practical experience, service costs and lack of staff were identified. Conclusion and relevance: In this exploratory work, attitudes towards involvement were overall favourable, however various levels of involvement were identified. Therefore, further work should investigate the extent of involvement and feasibility across different clinical areas. These findings add to the evidence base, the acceptability and development of pharmacy team involvement across various clinical areas. References and/or acknowledgements: No conflict of interest.